2021
DOI: 10.5851/kosfa.2021.e5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pig Breed and Processing Stage on the Physicochemical Properties of Dry-Cured Loin

Abstract: This study investigated the effect of pig breeds on the quality characteristics of dry-cured loins according to the processing stage. Physicochemical properties of 20 dry-cured processed loins with the different pig breeds (Berkshire vs Landrace × Yorkshire × Duroc (LYD; n=10)) and different processing stages (raw, curing, dry-ripened 15 day and 30 day) were analyzed. The pig breed influenced moisture content and pH with values of 59% and 53%, and 6.17 and 5.94, for Berkshire and LYD, respectively, at day 30. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…LH and LL, which were highly dehydrated, contracted more strongly, and cohesiveness increased as the dehydrated empty space naturally decreased. Seo et al (2021) also reported similar findings to ours.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…LH and LL, which were highly dehydrated, contracted more strongly, and cohesiveness increased as the dehydrated empty space naturally decreased. Seo et al (2021) also reported similar findings to ours.…”
Section: Resultssupporting
confidence: 91%
“…Lipid extraction was carried out according to Folch et al (1957) . Saponification, methylation, and gas chromatography (GC) learning conditions were employed by Seo et al (2021) . The fatty acid methyl etsers (FAME) were separated with GC (7890B, Agilent Technologies) equipped with a Supelco SP ® -2560 capillary GC column (100 m×0.25 mm×0.20 μm).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid extraction was conducted by Folch et al [ 13 ], as well as saponification, methylation, and gas chromatography under learning conditions employed by Seo et al [ 15 ]. The amount of fatty acids was expressed as a percent of total fatty acids.…”
Section: Methodsmentioning
confidence: 99%
“…chromatography under learning conditions employed by Seo [15]. The amount of fatty acids was expressed as a percent of total fatty acids.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The solubility of myofibrillar proteins in raw meat is an important processing property. Defective meat, such as PSE, has lower solubility of myofibrillar proteins, and consequently, its use results in quality deterioration of meat products [ 53 , 54 ]. Therefore, the selection of raw meat with high myofibrillar protein solubility is extremely important to manufacture low-salt meat products.…”
Section: Reduction Of the Ingredients Potentially Harmful When Overco...mentioning
confidence: 99%